Leucaena leucocephala (Lam.) de Wit: impactos sobre a vegetação nativa do Parque Nacional Serra de Itabaiana, Sergipe e modelagem de nicho climático - Silva, Francielly Oliveira da (2022)
Biological invasions (BI) are one of the main threats to global biodiversity and are responsible for generating substantial economic damage to agriculture and livestock. Given the seriousness of the effects of BI and the low availability of information about most species that cause this process, this study aimed to evaluate the impacts of the exotic invasive Leucaena leucocephala (Lam.) by Wit about the autochthonous flora of the National Park Serra de Itabaiana, Sergipe and to evaluate the current and future potential distribution for the species through climate niche modeling. To assess the impacts of L. leucocephala on the native vegetation of the study site, 20 plots were plotted, half in sites invaded by the species and the other half in non-invaded sites. Within these sampling units, individuals of all woody species were counted and with these data statistical analyzes were performed. In order to assess the potential distribution of the species, georeferenced occurrence points were obtained in the SpciesLink and GBIF databases. Analyzes were performed for the present and future time using bioclimatic variables obtained from Worldclim 2.0. In order to carry out the modeling, different algorithms were used to generate a consensual model. Forty-one species were sampled in the invaded environment and 18 in the uninvaded environment. According to the analyzes carried out, there are significant differences in composition, richness and diversity among the studied environments. The results of the modeling analysis indicated high susceptibility of occurrence for the species throughout the Brazilian territory. The results also suggest that its area of potential occurrence could increase if predictions of climate change for the next years materialize.